An Application of a Dual-Module VSG Based on QPR and Virtual Impedance in Three-Phase Unbalanced Power Grids - Liping Fan; Mingjun Wang (Energies)
As an innovative solution, the virtual synchronous generator (VSG) facilitates the seamless incorporation of renewable energy into power grids. It also exhibits the ability to reconfigure system inertia and deliver damping effects, thereby assuming a progressively vital role in contemporary power systems. Three-phase voltage imbalance, a common phenomenon in power grids, causes current distortion. Imbalance, a common phenomenon in power grids, causes current distortion in VSG outputs, thereby affecting power quality. Therefore, ensuring symmetrical current injection into the grid has become a critical challenge in grid-connected technology. To resolve this challenge, a dual-module VSG control scheme is introduced, enabling precise regulation of the VSG’s power delivery. This approach effectively distinguishes and separately manages the positive-sequence and negative-sequence power outputs of the VSG. Furthermore, virtual impedance and quasi-PR control are incorporated into the current control loop to achieve zero negative-sequence power output from VSG, ensuring a stable power supply. Simulation results validate the reliability of this approach, providing both a theoretical foundation and practical evidence for its future application.